Kto, kogo i do czego chce przekonać w Politei Platona? (O dwóch zderzających się nowych interpretacjach) - Zygmuntowicz, Dorota (In Gremium. Studies in History, Culture and Politics, 2022)
The article discusses James L. Kastely’s, The Rhetoric of Plato’s Republic. Democracy and the Philosophical Problem of Persuasion (2015), in the context of later reading of the Republic by Jacob Howland, Glaucon’s Fate. History, Myth, and Character in Plato’s Republic (2018). The comparative background is the process of the act of persuasion: according to Howland, ineffective against Glaucon, and according to Kastely, affective in the world as it is. In its conclusion, the paper submits that the degree of rightness of these two colliding interpretations is largely hided in the profile of the addressees/ the first recipients of the dialogue (in their persuasive sensitivity) and in the way of transmitting 10 books of the Republic.